Remark
The idea here is to take any two successive terms and divide one by the other. which is the divisor and which the dividend will be discussed below.
Step One
Set up the ratio for the common ratio between terms that come one after another.
Mathematically this is written as
r =
![(t_(n+1))/(t_n)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ey5nc53x5cokofgvh4o3oixfd7wgnl9rwy.png)
So just to see how this looks
t_(n + 1) = 3
t_n = 9
r =
![(t_(3))/(9)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/z6un0o9n5y44y1v5d61dq4zd2ubt9fejob.png)
r = 1/3
Does this work for other examples? Let's try a more complicated looking one.
t_(n) = 1/9
t_(n+1) = 1/27
r = t_(n + 1) / t_n
r =
![( (1)/(27) )/( (1)/(9) )](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ib38lg2d39e15tnwjb8mfxeaepisuvw3tx.png)
r =
![(1)/(27)* (9)/(1)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/e2zcil62prd6brbsm2h1yqsv8u393tu6i4.png)
r = 1/3